2014
DOI: 10.1038/ncomms6319
|View full text |Cite
|
Sign up to set email alerts
|

Formation and maintenance of neuronal assemblies through synaptic plasticity

Abstract: The architecture of cortex is flexible, permitting neuronal networks to store recent sensory experiences as specific synaptic connectivity patterns. However, it is unclear how these patterns are maintained in the face of the high spike time variability associated with cortex. Here we demonstrate, using a large-scale cortical network model, that realistic synaptic plasticity rules coupled with homeostatic mechanisms lead to the formation of neuronal assemblies that reflect previously experienced stimuli. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
446
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(468 citation statements)
references
References 64 publications
21
446
1
Order By: Relevance
“…Unless the changes caused by the synaptic plasticity support the WM function (i.e., retune the network dynamically to better generate persistent activity), then that function may be lost quickly. Consequently, an important line of inquiry, with some advances already made (Litwin-Kumar & Doiron 2014, Renart et al 2003, Savin & Triesch 2014, Zenke et al 2015), is to understand how ongoing synaptic plasticity can create reliable and long-lasting WM networks.…”
Section: Functional Constraints On Persistence-generating Mechanismsmentioning
confidence: 99%
“…Unless the changes caused by the synaptic plasticity support the WM function (i.e., retune the network dynamically to better generate persistent activity), then that function may be lost quickly. Consequently, an important line of inquiry, with some advances already made (Litwin-Kumar & Doiron 2014, Renart et al 2003, Savin & Triesch 2014, Zenke et al 2015), is to understand how ongoing synaptic plasticity can create reliable and long-lasting WM networks.…”
Section: Functional Constraints On Persistence-generating Mechanismsmentioning
confidence: 99%
“…Statistical correlations in natural scenes might therefore lead to wiring of subnetworks under an activity-dependent mechanism such as spike-time dependent plasticity (STDP) [92][93][94][95][96]. Along these lines, examinations of the development of specific excitatory connections after eye opening found that similarities in feedforward input were progressively encoded in specific excitatory connections [22].…”
Section: Feature Binding To Detect Higher-order Visual Statisticsmentioning
confidence: 99%
“…This question has been repeatedly addressed by theorists and modellers, and their work typically indicates that without some form of stabilization of firing rates or synaptic weights, network models that can store memory patterns in recurrent synaptic strength become unstable, typically in the direction of activity being too high [1][2][3][4]. These runaway increases in activity emerge from the fact that most Hebbian strengthening mechanisms are dependent on coincident firing between the pre-and post-synaptic neurons, and this process involves a positive feedback loop: namely, the more frequent coincident activity in a group of neurons is, the more likely that synapses connecting these neurons are strengthened.…”
Section: The Necessity Of Stabilizing Mechanismsmentioning
confidence: 99%
“…What characteristics of the circuit are being stabilized by these mechanisms that make this process homeostatic? There is experimental evidence for three balance parameters: firing rate homeostasis, subthreshold activity homeostasis, and synaptic weight homeostasis, and any of these three parameters, when incorporated into the appropriate theoretical model, may stabilize the network to prevent pathological neuronal dynamics or learning [1,3,4,[47][48][49][50][51][52][53][54][55][56][57][58]. First, firing rate homeostasis was initially described with the first experimental evidence of synaptic scaling [5], and altering cellular [59] and network firing rate has consistently evoked a response of the induction of homeostatic mechanisms [5,7,11,12,29,60].…”
Section: Parameters Of Homeostatic Balancementioning
confidence: 99%